UPAYA PENINGKATAN KEBERSIHAN GIGI DAN MULUT MELALUI UPAYA PROMOTIF DAN PREVENTIF PENYAKIT GIGI DAN MULUT DI SD N 1 CELUK - I Made Budi Artawa (Poltekkes Kemenkes Denpasar, 2020)
Abstract The results of the identification of problems with 112 State elementary school students 1 Celuk average knowledge of maintenance of dental and mouth health criteria failed, oral hygiene criteria were moderate, brushing skills were incorrect criteria. So that the problem